Monocyte-derived dendritic cells display a highly activated phenotype and altered function in patients with familial Mediterranean fever. (27th April 2020) - Funk, T; Fuchs, A R; Altdörfer, V S; Klein, R; Autenrieth, S E; Müller, M R; Salih, H R; Henes, J; Grünebach, F; Dörfel, D
Summary: Dendritic cells (DCs) are sentinels of the immune system that bridge innate and adaptive immunity. By capturing antigens in peripheral tissue, processing and presenting them with concurrent expression of co-stimulatory molecules and cytokine secretion they control and modulate immune reactions. Through pattern recognition receptors, DCs sense molecules that are associated with infection or tissue damage, frequently resulting in the formation of inflammasomes upon intracellular stimulation. The inherited autoinflammatory familial Mediterranean fever (FMF) is associated with deregulated activity of the pyrin inflammasome leading to acute inflammatory episodes. However, differentiation and function of DCs in this disease are as yet unclear. Therefore, we first determined DC subpopulation frequency in peripheral blood of a cohort of FMF patients. Joint evaluation without classification according to specific patient characteristics, such as mutational status, did not disclose significant differences compared to healthy controls. For the further examination of phenotype and function, we used immature and mature monocyte-derived DCs (imMo-DCs, mMo-DCs) that were generated in vitro from FMF patients. Immunophenotypical analysis of imMo-DCs revealed a significantly elevated expression of CD83, CD86 and human leukocyte antigen D-related (HLA-DR) as well as a significant down-regulation of CD206, CD209 and glycoprotein NMB (GPNMB) in our FMF patient group. Furthermore, FMF imMo-DCs presented a significantly higher capacity to migrate and to stimulate the proliferation of unmatched allogeneic T cells. Finally, the transition towards a more mature, and therefore activated, phenotype was additionally reinforced by the fact that peripheral blood DC populations in FMF patients exhibited significantly increased expression of the co-stimulatory molecule CD86. Graphical Abstract: